Analysis Of Obstacles And Opportunities For Digital Technology Adoption For The Women Tailor Community In The City Of Surabaya - silvie Silvie; Muhammad Ahmi Husein (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This article investigates the obstacles and opportunities in digital technology adoption among women tailors in Surabaya, Indonesia a dynamic community-based entrepreneurship sector celebrated for traditional sewing expertise yet challenged by post-pandemic demands to modernize. These entrepreneurs must integrate design applications (e.g., IbisPaint, Procreate, CorelDRAW, 3D CAD, Pinterest, Canva, Rich Peach, Adobe Illustrator, Gemini AI) and ecommerce platforms (e.g., Shopee, Tokopedia, E-Peken), alongside social media tools (e.g.,Instagram, WhatsApp). However, generational mindsets, heavy domestic responsibilities, and cultural loyalty to manual methods exacerbate the digital gender gap, reflected in lower digitalization rates for female MSMEs (60.5%) versus males (63%) Positioning Surabaya's women tailors as a unique case for examining digital adoption amid social barriers and community dynamics, this study employs a qualitative interpretive phenomenological design. Data from semi-structured interviews with 15 expert informants women tailors aged 20–61years operating businesses for at least two years across Surabaya communities were analyzed thematically using NVivo 12 until saturation.Findings highlight community support via training and peer sharing as a key accelerator for adapting to design and sales tools. Conversely, social mindset barriers among those over 40 and inconsistent motivation impede full transitions to e-commerce and advanced digital workflows, underscoring the need for targeted interventions.